Epicatechin attenuates lead (Pb)-induced cognitive impairment in mice: regulation on Nrf2 signaling pathway, and interference on the interaction between Pb with albumin - Dai Cheng; Qianqian Yu; Kexin Zhu; Dingdong Bu; Zijian Wu (Food Science and Human Wellness)
Epicatechin (EC) was used in this study to antagonize the cognitive dysfunction caused by lead (Pb) exposure in mice. Eight-week-old male Kunming mice were treated with PbCl2 (20 mg/kg) and/or EC (50 mg/kg) by gavage administration for 4 weeks. Morris water maze test showed that EC could improve memory dysfunction induced by Pb. EC antagonized Ca2+ overload, activated Nrf2 signaling pathway and reduced the accumulation of Pb in the brain and serum, which suggested that EC might alter Pb distribution in mice. In vitro, spectroscopic analysis, potentiometric titration and docking studies were applied to inquiry into the interaction between bovine serum albumin (BSA) and Pb2+ in presence or absence of EC. EC was proved to chelate Pb2+ and reduced the interaction between BSA and Pb2+. In summary, EC might protect Pb-induced cognitive impairment by activating Nrf2 signaling pathway, and suppressing Pb accumulation via interference on the binding of Pb to albumin.